Answer:
g(4)=f(2)
Step-by-step explanation:
f(2)=3(2)-1
f(2)=6-1
f(2)=5
We then get:
g(x)=f(2)
subsitute 5 for f(2)
g(x)=5
now solve
5=2x-3
add 3
8=2x
divide 2
4=x
so the answer is x=4 or
g(4)=f(2)
I would belive its great because if you have 4/5 of a pie compared to 7/12 of a pie having 4/5 would be more of the pie , I hope that helped that's how I have to think about fractions
It would be A or B
but not D,C
The answer would be -1/6 or -0.166667
Answer:
9yx
Step-by-step explanation:
product means multiply.
nine, y and x
9yx